Peningkatan keselamatan bersama melalui kerjasama dua hala Malaysia dan negara-negara jiran - Ruhanas Harun (Penerbit UKM, 2009)
Malaysia is centrally situated in Southeast Asia and shares direct borders with five countries of the region, namely Breunei, Thailand, Singapore Indonesia and the Philippines. Currently one of the major challenges to its security is its porous borders which are difficult to control. For more than forty years, Malaysia has struggled against communist insurgency, a threat also shared by its neighbours. After the end of the communist insurgency in 1989 and the end of the Cold War, the preoccupation of security turned to non traditional security issues such as illegal immigrants, transnational crimes and the spillovers of political instability in the neighbouring countries, in addition to the issue of international terrorism in the aftermath of September 11 2001 event. To cope with all these security threats, as in the past, Malaysia adopted a policy of cooperation with the neighbours involved. This paper aims to analyse some of the main security issues that preoccupied and continues to occupy the Malaysian state and the bilateral cooperation with Philippines, Indonesia and Thailand in dealing with the security threats. It will aslo discuss some of the challenges involving bilateral security relations.